Effect of Decreasing Biological Lability on Dissolved Organic Matter Dynamics in Streams. Issue 2 (17th February 2021) - Li, Angang; Drummond, Jennifer D.; Bowen, Jennifer C.; Cory, Rose M.; Kaplan, Louis A.; Packman, Aaron I.
Abstract: Respiration of dissolved organic matter (DOM) in streams contributes to the global CO2 efflux, yet this efflux has not been linked to specific DOM sources and their respective uptake rates. Further, removal of DOM inferred from longitudinal concentration gradients in river networks has been insufficient to account for observed CO2 outgassing. We hypothesize that understanding in‐stream dynamics of DOM, which is a heterogeneous mixture spanning a wide range of biological labilities, requires considering that DOM lability decreases during downstream transport. To test this hypothesis, we paired seasonal bioreactor measurements of DOM biological lability with whole‐stream tracer data from White Clay Creek, Pennsylvania, USA, and used a particle‐tracking model to predict in‐stream DOM dynamics. The model simulates continuous inputs of DOM and uses storage time in the stream bioactive regions plus kinetic parameters from bioreactors to assess differential uptake of DOM fractions (i.e., fractionation) in the stream. We compared predictions for in‐stream dynamics of bulk DOM concentration (quantified as dissolved organic carbon) and fluorescent DOM components. Our model‐data synthesis approach demonstrates that more labile fractions of DOM in stream water preferentially originate and are consumed within short travel distances, causing spiraling metrics to change with downstream distance. Our model can account for local sources of rapidly cycled labile DOM, providing a basis for improved interpretation of DOM dynamics in streams that can reconcile apparent discrepancies between respiratory outgassing of CO2 and longitudinal DOM concentration gradients within river networks. Plain Language Summary: In streams, microorganisms metabolize naturally occurring organic molecules dissolved in streamwater and release carbon dioxide, which contributes to global carbon emissions. These organic molecules are part of a complex and diverse mixture including thousands of different chemical compounds that differ widely in susceptibility to biodegradation. We developed a mathematical model to describe changes in the pool of organic molecules flowing downstream, incorporating field and laboratory measurements of biological degradation of organic molecules and information about water flow into and out of zones that promote biological activity. We demonstrated that the molecules more susceptible to biodegradation are preferentially metabolized and become depleted over short travel distances downstream, while organic species less susceptible to biodegradation are transported farther downstream. Our model improves understanding of the transport and metabolism of organic molecules in streams, and explains factors that control the overall concentration of organic molecules in streams and rivers. The results help to reconcile discrepancies between estimates of carbon dioxide outgassing from streams and observations of organic carbon concentrations within streams. Key Points: Dissolved organic matter (DOM) biological lability decreases with residence time in bioactive regions of the stream (defined as bioactive residence time ) Decreasing biological lability, exchange into and residence times in bioactive regions influence in‐stream DOM dynamics Model predictions show how the distribution of DOM fractions (i.e., fractionation) and spiraling metrics depend on in‐stream location